A influência da morfologia do MgO nas propriedades catalíticas do SiO2/MgO para a formação de 1,3-Butadieno a partir de etanol - Souza, André Machado Ribeiro de (2016)
Ethanol has been largely studied in the past few decades as a substitute to fossil fuels in the synthesis of a large variety of chemicals. 1,3-Butadiene, one of these compounds, is an important chemical intermediate and also a monomer for some polymers such as synthetic rubbers. It is mainly produced as a by-product from naphtha steam cracking, which has ethylene as the major product. As crude oil prices have been fluctuating in the latest years and with the discovery of shale gas in the US, a promising source for ethylene, there is an urgency for developing alternative routes to produce 1,3-Butadiene. Several studies have been carried since the 1940s trying to create viable processes and using many different catalysts, indicating MgO/SiO2 - with or without the addition of transition metals - as being the most promising one. However, there is still a lot of missing information on how does the interaction between silica and magnesia affect the yields and selectivity. In the present work it was studied how the morphology of the MgO affects the interaction with the SiO2 to generate active sites. The MgO with different morfologies were synthesized and then wet-kneaded with SiO2 to provide catalysts with different MgO/SiO2 ratio. The samples were calcined and catalytic tests were carried out. X-Ray Diffraction, Temperature Programmed Desorption of CO2 and Scanning Electron Microscopy were also performed on the catalysts. The obtained micrographs for the oxides confirmed the successful preparation of different morphologies, and the results for catalytic tests showed that there is some influence from the morphology over conversion and selectivity of SiO2/MgO. For the MgO morphologies at the temperature of 425 oC, ethanol conversions between 11.7% and 21.9% were obtained for different samples, with selectivities for butadiene between 5.6% and 30.4%. For SiO2/MgO catalysts, in the same temperature, different yields were obtained for distinct morphologies and Mg:Si ratios. For 3:1 catalysts, yields between 21.5% and 34.3% were observed, while for 7:1 catalysts the yields vary from 18.5% to 35.4%. Catalytic properties could not be clearly correlated to the TPD-CO2 and specific surface area, indicating that they are dependant on a complex set of factors, among them the accessibility of the surface for the SiO 2 contact. Variation of the silica content for all morphologies showed that the SiO2/MgO ratio is extremely important for the preparation of active and selective catalysts for the production of 1,3-butadiene.